KEANEKARAGAMAN ANGGREK DI CAGAR ALAM DAN TAMAN WISATA ALAM TELAGA WARNA, PUNCAK, BOGOR - Siti Suryani Tahier; Tri Saptari Haryani; Sri Wiedarti (Universitas Pakuan, 2018)
The existence of orchids is often threatened with extinction that can be caused by natural damage. In addition, the continuous harvesting of orchids from nature without considering its sustainability can threaten the extinction of orchids in a region. There is a need for knowledge about the diversity of orchids so that it can be the basis of conservation in a region specifically nature reserve and Nature Park Bogor. Research using transect methods and data collection conducted using field observation techniques. The observation area consists of three locations altitude: 1400, 1500 and 1600 m above sea level . There are 27 species of orchids consisting of 19 genera. From the calculation of important value index (INP), the dominating type is found at altitude 1400 and 1500 m above sea level is Ceratostylis crassifolia, While at height and 1600 m DPL is Liparis compressa. Index diversity of type in the research site with a height of 1400 m DPL is moderate and at an altitude of 1500 and 1600 m DPL is high. The spread index is known that the pattern of spreading orchid species in three research locations has a clumped group spread pattern.